Employment Perception among Undergraduate Students in The Hospitality Industry - syed a. kadir, syed shikh; Abdul Razzaq, Abdul Rasid; Abdul Rahman, Abdul Wafi; Harun, Hairuddin; Rohiat, Mohd Akmal; Raden Ismail, Raden Mohd Farhan Helmy; Badar, Noraida Darweena (Research and Innovation in Technical and Vocational Education and Training, 2021)
The growth of the industry and the growing competition, this indicates that the industry is thriving. Therefore, Malaysia needs more skilled labor to meet the needs of the industry. The public and private sectors need to continue to play a role in providing hospitality as they are believed to have the potential to produce graduates who are ready to be absorbed by the industry. There are too many issues related to hospitality industry jobs so graduates need to be well prepared in terms of knowledge, skills and experience. In addition, students need to constantly think about the factors that influence them to work in the hospitality industry. The purpose of this study was to study the students’ perception of the catering program, Faculty of Technical and Vocational Education (FPTV), UTHM on employment in the field of hospitality upon completion of Bachelor’s degree. The chosen methodology is to use quantitative data which is a survey study to answer the research question. Questionnaires are instruments used to obtain research data. The results of this study look at the perceptions of 78 students in catering programs, and can help them identify industry needs for workers.